Kaurene diterpene induces apoptosis in U87 human malignant glioblastoma cells by suppression of anti-apoptotic signals and activation of cysteine proteases - Lizarte Neto,F.S. (2013)
Gliomas are the most common and malignant primary brain tumors in humans. Studies have shown that classes of kaurene diterpene have anti-tumor activity related to their ability to induce apoptosis. We investigated the response of the human glioblastoma cell line U87 to treatment with ent-kaur-16-en-19-oic acid (kaurenoic acid, KA). We analyzed cell survival and the induction of apoptosis using flow cytometry and annexin V staining. Additionally, the expression of anti-apoptotic (c-FLIP and miR-21) and apoptotic (Fas, caspase-3 and caspase-8) genes was analyzed by relative quantification (real-time PCR) of mRNA levels in U87 cells that were either untreated or treated with KA (30, 50, or 70 µM) for 24, 48, and 72 h. U87 cells treated with KA demonstrated reduced viability, and an increase in annexin V- and annexin V/PI-positive cells was observed. The percentage of apoptotic cells was 9% for control cells, 26% for cells submitted to 48 h of treatment with 50 µM KA, and 31% for cells submitted to 48 h of treatment with 70 µM KA. Similarly, in U87 cells treated with KA for 48 h, we observed an increase in the expression of apoptotic genes (caspase-8, -3) and a decrease in the expression of anti-apoptotic genes (miR-21 and c-FLIP). KA possesses several interesting properties and induces apoptosis through a unique mechanism. Further experiments will be necessary to determine if KA may be used as a lead compound for the development of new chemotherapeutic drugs for the treatment of primary brain tumors.